Transfer effects and permeable boundaries: an empirical study of the effects of commuting stress on employees' work and life - Mohd Mahudin, Nor Diana (Universiti Malaysia Sabah, 2012)
The impact of commuting stress has been addressed by only a few studies, most of which have been conducted in developed countries. Far less research has looked at the subjective, psychological effects of commuting on employees’ wellbeing within the Malaysian context. This paper describes a study which investigates the effects of commuting stress on commuters’ individual life and work domains. Data were collected from 660 commuters through a questionnaire survey and explored using correlation and regression analysis. The results show that longer commutes are significantly associated with a greater increase in commuting stress. They also reveal that the strain of commuting affects commuters’ reports of somatic symptoms of ill health and commute displeasure. In addition, commuting stress is found to affect commuters’ intention to quit their job but not in terms of their job or life satisfaction. Drawing on these results, theoretical and research implications that would lend support for future commuting stress research, particularly in Malaysia, are suggested.